Dự thảo Luật Quản lý, sử dụng vũ khí, vật liệu nổ và công cụ hỗ trợ (Dự thảo lần 8) - Quốc hội (2017)
Dự thảo Luật Quản lý, sử dụng vũ khí, vật liệu nổ và công cụ hỗ trợ (Dự thảo lần 8) gồm 8 chương, 75 điều.